Rapid Identification of Common Poisonous Plants in China Using DNA Barcodes - Wang, Jie; Zhao, Jinquan; Yu, Weisen; Wang, Shuangyu; Bu, Shuhua; Shi, Xuexiang; Zhang, Xiuyun (Frontiers in Ecology and Evolution, 2021)
Toxic plants have been a major threat to public health in China. However, identification and tracing of poisoned species with traditional methods are unreliable due to the destruction of plant morphology by cooking and chewing. DNA barcoding is independent of environmental factors and morphological limitations, making it a powerful tool to accurately identify species. In our study, a total of 83 materials from 26 genera and 31 species of 13 families were collected and 13 plant materials were subjected to simulated gastric fluid digestion. Four markers (rbcL, trnH-psbA, matK, and ITS) were amplified and sequenced for all untreated and mock-digested samples. The effectiveness of DNA barcoding for the identification of toxic plants was assessed using Basic Local Alignment Search Tool (BLAST) method, PWG-Distance method, and Tree-Building (NJ) method. Except for the matK region, the amplification success rate of the remaining three regions was high, but the sequencing of trnH-psbA and ITS was less satisfactory. Meanwhile, matK was prone to be more difficult to amplify and sequence because of simulated gastric fluid. Among the three methods applied, BLAST method showed lower recognition rates, while PWG-Distance and Tree-Building methods showed little difference in recognition rates. Overall, ITS had the highest recognition rate among individual loci. Among the combined loci, rbcL+ITS had the highest species recognition rate. However, the ITS region may not be suitable for DNA analysis of gastric contents and the combination of loci does not significantly improve species resolution. In addition, identification of species to the genus level is sufficient to aid in the clinical management of most poisoning events. Considering primer versatility, DNA sequence quality, species identification ability, experimental cost and speed of analysis, we recommend rbcL as the best single marker for clinical identification and also suggest the BLAST method for analysis. Our current results suggest that DNA barcoding can rapidly identify and trace toxic species and has great potential for clinical applications. In addition, we suggest the creation of a proprietary database containing morphological, toxicological and molecular information to better apply DNA barcoding technology in clinical diagnostics.